Long-term effect of nutrients on castor (Ricinus communis L.) productivity, soil fertility, nutrient uptake and nutrient-use efficiency in rainfed Alfisols: LONG-TERM EFFECT OF NUTRIENTS ON CASTOR IN RAINFED ALFISOLS - P RAMESH; I Y L N MURTHY; CH V HARIPRIYA (Journal of Oilseeds Research, 2013)
A fixed-plot field experiment was conducted since 2005 to study the long-term effect of nutrients on the productivity, soil fertility, nutrient uptake and nutrient-use efficiency of castor (Ricinus communis L.) in castorsorghum (Sorghum bicolor) cropping system in rainfed Alfisols of Andhra Pradesh. Application of recommended dose offertilizers, RDF (60-40-30 kg NPK/ha) + 5 t/ha farm yard manure (FYM) recorded significantly higher yield attributes, seed (1645 kg/ha) and oil yield (817 kg/ha) of castor compared to RDF (1306 kg/ha) but was comparable with integrated use of 75 % NPK + 25 % N through FYM (1427 kg/ha). Imbalanced application of N alone or NP or 50 % NPK and control plots recorded significantly the lowest castor seed yields. At the end of six years of cropping (2011), the treatment RDF-NPK + 5 t/ha FYM significantly improved the soil organic carbon (0.38 %) and resulted in a positive balance of 42, 12.4 and 80 kg/ha of available soil N, P and K besides improving the nutrient uptake of castor (65.1, 10.63 and 33.2 kg/ha of N, P and K, respectively). Agronomic efficiency of nutrients (N, P and K) was found higher in the treatment, 75 % RDF + 25 % N through FYM. However, apparent recovery of N, P and K was highest in NPK + 5 t/ha FYM treatment.